THE EFFECT OF ITERATIONS, COLLABORATION, AND DESIGNING GEOGEBRA MODULES ON IN-SERVICE SECONDARY MATHEMATICS TEACHERS - Dr Houssam Kasti, Professor Zsolt Lavicza, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The ability to design technological activities or applets is one of the new challenges for teachers in the context of digital learning. Technology teacher training should convert from presenting solutions for teachers, to assist them to become better designers in resolving their own problems. To be able to do that this study used design-based research methodology and worked collaboratively and iteratively, through three iterations with the use of the powerful open-source software GeoGebra. Three theories were used in this study to contribute to our goals: 1) Technological Pedagogical Content Knowledge (TPACK); 2) the Diffusion of Innovation Theory; and 3) the Zone Theory. The study is based on a qualitative multiple case study design with four in-service secondary mathematics teachers (three females and one male) with diverse backgrounds. Analysis of the data indicated improvements of participants in their utilization of GeoGebra in their practices as well as in their TPACK integration levels. Unlike the fast improvement in participants’ TPACK, the change in practices was slow, but considered sustained. In addition, effects of collaboration and iterations with researchers decreased hinderances in GeoGebra integration and improved some of the assistance factors. With this study we aim to contribute to both theory and practices for teacher professional development.